Sustainable Rote Horse Development Strategy: An Integrative Approach to Technical, Social, and Economic Aspects in Local Livestock Management - Randu, Melkianus Dedimus Same; Batafor, Gregorius Gehi; Menoh , Yori Raimona; Deko, Maria Karolina; Ndolu, Devi Anthonia Juliana; Zebua, Cipta Kasih Novilita (Jurnal Ilmu-Ilmu Peternakan, 2026)
The Rote horse is a local genetic resource from the Rote Ndao Regency, East Nusa Tenggara, which has important socio-cultural, ecological, and economic value to the community. However, its utilisation of Rote horses is relatively low as the rapid expansion of motorised transportation has shifted their role in traditional practices and local livelihoods. This situation may limit their contribution to the local economy and raise concerns about the conservation and long-term sustainability of this local livestock genetic resource. This study aimed to formulate a sustainable development strategy for the Rote horse using an integrated approach that considers the technical, social, and economic aspects of local livestock management. A mixed-method approach was used, involving 96 respondents through structured interviews, focus group discussions (FGDs), and participant observations. SWOT, TOWS, and QSPM analyses identified and prioritized development strategies. The study results show that the main strengths lie in the ecological adaptation of the Rote horse, cultural values (Hu's rituals), and the availability of natural resources. Weaknesses stem from limited annual feed supply and minimal technology adoption. Tourism potential and institutional support represent strategic opportunities, while policy barriers and supply fluctuations pose threats. The recommended priority strategy involves the development of eco-cultural tourism centred on the Rote horse (18.45), which achieved the highest score in the QSPM analysis. This study highlights the significance of integrating cultural values and institutional support, and of strengthening the tourism sector, as a roadmap towards a sustainable Rote horse breeding system while strengthening local economic resilience and genetic conservation.